Memahami Tradisi Adi Beren dalam Budaya Dayak Krio sebagai Pengembangan Pendidikan Karakter Kaum Muda Krio - Fransiskus Ajai; Pabianus Prayoga; Edmundo Harry Satria Putra (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2026)
The focus of this research is to understand the Adi Baren tradition as character education for Krio youth. Dayak Krio culture has various traditions that are rich in noble values, one of which is the Adi Beren tradition. The Dayak Krio tradition is a traditional ceremony that aims to strengthen social ties and instil moral values in the young generation of Dayak Krio in order to form young Krio people who have sensitivity to the needs of others and care for the environment. This paper aims to understand the meaning and significance of the Adi Beren tradition in the development of character education for Krio Dayak youth. The research method used is qualitative method from various sources such as scientific journals, books that can support this paper. The results showed that the Adi Beren tradition contains noble values such as solidarity, mutual cooperation, responsibility, and respect for nature. These values can be integrated in the development of character education for Krio Dayak youth, so as to strengthen cultural identity and prepare the next generation with noble character.